Swamedikasi diabetes mellitus dengan daun ceplikan (Ruellia tuberosa L.): kajian kemanfaatan pada profil lipid serum secara praklinik - Ety Yuni Ristanti; Wiryatun Lestariana; Lily Arsanti Lestari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2009)
Background: Self-medication by using ceplikan leaves (Ruellia tuberosa L.) has been practiced in society for many times in the after-boiled form. It had been proved that liquid extract of ceplikan leaves (Ruellia tuberosa L.) was able to reduce blood glucose level on diabetic rat. It is also well known among diabetes mellitus patient that it has following effect on increasing triglyceride and reducing HDL-cholesterol level.Objective: This research was aimed to give scientific evidence on the society habit on self-medication by using ceplikan leaves (Ruellia tuberosa L.) by examining its oral administration on serum lipid profile pre-clinically.Method: Two months old Rattus novergicus within average weight of 150-200 g were divided into experimental and control groups. The control group consisted of 6 normal rats; while the experimental group consisted of 24 alloxan induced-diabetic rats. The experimental groups were divided into four groups i.e. non-treatment group and oral administrations of Ruellia tuberosa L. liquid extract with different concentrations that were 1.6 mg, 3.2 mg, and 6.4 mg, respectively. The feeds were given ad libitum. The oral administrations of Ruellia tuberosa L. liquid extract were given everyday for 30 days. In the end of the treatment, all rats were fastened and the blood was taken from the eye and being observed for its serum lipid profile. The data were analyzed statistically by using ANOVA and Tukey’s HSD mean difference tests.Results: The results showed that oral administration of 3.2 mg Ruellia tuberosa L. liquid extract was significantly reduced triglyceride and LDL-cholesterol level (p < 0,05) and increased HDL-cholesterol level (p < 0,05).Conclusion: The 3.2 mg of Ruellia tuberosa L. liquid extract was able to reduce triglyceride and LDL-cholesterol level and increase HDL-cholesterol level. Moreover, ceplikan leaves (Ruellia tuberose L.) could be taken as traditional drugs in a non-formal way with control on dietary intake and regular physical exercise.